Being-Towards-Death: Anxiety and Hope in the Art of Western Modern Literature - Yuanhua Wu (Forest Chemicals Review, 1970)
This paper takes western modern literature as the research object, and starts with the anxiety phenomenon in the art of western modern literature, and analyzes the real features of western literature and art by using the research methods of analysis and literature research. Exploring the "Reconstruction of value” of western literature and art reveals that the literary thought of "Being towards death" in in the art of western modern literature is not just a literal expression, but a search for the meaning of life.